2014
DOI: 10.4103/0972-124x.128195
|View full text |Cite
|
Sign up to set email alerts
|

Fluorosed fibroblast attachment on fluorosed and nonfluorosed teeth after SRP and EDTA root biomodification

Abstract: Background:Fluorosis causes mineralization changes in the tooth and can lead to morphologic alterations of fibroblasts. To understand the effect of fluorosis on periodontal healing, the initial step during healing, such as fibroblast attachment to the root surface, needs to be evaluated. Hence, the objective of the present study was to study the attachment of fluorosed fibroblasts on the fluorosed and nonfluorosed root fragments.Materials and Methods:A total of 56 fluorosed and nonfluorosed, periodontally heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…The results of the current study showed that the cell viability of the fibroblasts attached to roots treated with scaling only was the highest compared with all other groups, and that scaled teeth treated with EDTA or CHX did not enhance cell attachment. This is in agreement with other studies which demonstrated that SRP is the standard requirement for attachment of fibroblasts and that root treatment with EDTA did not enhance cell viability or attachment over SRP alone when measured using either stereomicroscope or scanning electron microscope ( Girotra and Vandana, 2014 , Lima et al, 2016 ). Additionally, other researchers stated that the exposure of fibroblasts to ≥0.02% CHX reduced the survival rate of the cells in vitro ( Liu et al, 2018 ).…”
Section: Discussionsupporting
confidence: 92%
“…The results of the current study showed that the cell viability of the fibroblasts attached to roots treated with scaling only was the highest compared with all other groups, and that scaled teeth treated with EDTA or CHX did not enhance cell attachment. This is in agreement with other studies which demonstrated that SRP is the standard requirement for attachment of fibroblasts and that root treatment with EDTA did not enhance cell viability or attachment over SRP alone when measured using either stereomicroscope or scanning electron microscope ( Girotra and Vandana, 2014 , Lima et al, 2016 ). Additionally, other researchers stated that the exposure of fibroblasts to ≥0.02% CHX reduced the survival rate of the cells in vitro ( Liu et al, 2018 ).…”
Section: Discussionsupporting
confidence: 92%
“…Neha G and Vandana [12] conducted a study to evaluate the attachment of fluorosed fibroblasts on the fluorosed and nonfluorosed root fragments and concluded that SRP proves to be a standard requirement for fibroblast attachment to occur both in fluorosed and nonfluorosed roots. Although there was no significant difference in attachment between SRP and SRP + EDTA among fluorosed roots, EDTA does not seem to be a promising agent for root bio-modification in fluorosed roots in a given concentration and time of treatment.…”
Section: Study To Evaluate the Attachment Of Fluorosed Fibroblasts Onmentioning
confidence: 98%
“…The institutional studies presented above apart from being preliminary were all self-funded and carried out with the single motive of exploring the effect of fluorosis on the periodontium. The age group of the population in these studies was between 15 and 74 years for epidemiological survey [2] and a constant 18-25 years (periodontally healthy teeth extracted due to orthodontic reasons) in in vitro studies [3][4][5][6][7][8][9][10][11][12][13][14][15] that allows for better comparisons of study results within the same study population. In an epidemiological survey, a strong association of occurrence of periodontal disease in high-fluoride areas was found.…”
Section: Effect Of 980-nm Diode Laser-aided Circumferential Supracresmentioning
confidence: 99%
See 1 more Smart Citation
“…The purpose of the EDTA conditioning, in this study, was to demineralize the root and removal of smear layer produced due to instrumentation to facilitate fibroblast adhesion and locomotion by collagen exposure [19,20]. The in vitro and in vivo effects of EDTA root biomodification are not consistent evident [20,21].…”
Section: Discussionmentioning
confidence: 99%